Wireless hybrid sensor network for agriculture monitoring - Blokhin Yu. I.; Blokhina S. Yu. (BIO Web of Conferences)
This paper presents a hybrid wireless sensor network (WSN) for agricultural monitoring. The system was set up to facilitate monitoring of crop state, weather conditions and soil characteristics in real time in accordance with the application’s needs of three communication technologies: IEEE 802.15.4/ZigBee, WIFI and LTE 4G as a part of Internet of Things (IoT). Two types of sensor nodes were developed: a mobile sensor node with an optical camera and a sensor node with a soil moisture and temperature sensors. A base station operating as network coordinator was designed to control meteorological characteristics. The software of the sensor nodes has been written on the MicroPython language, the Pi Pico controller provides control and polling of peripheral devices in accordance with a given algorithm. At the base station, the data incoming from the sensor nodes have been processed with the calculation of soil parameters based on pre-set calibrations. After being processing, the data has been transmitted to the server. A Raspberry Pi 3B microcomputer and Java software are used to process data and manage the base station weather sensors. The interaction with the weather sensors has been completed in the frame of Pi4J project using the WiringPi libraries. On the server, the data has been distributed among the corresponding tables in the Agro database, each record has been assigned a unique identifier, date and time. PostgreSQL was chosen as the database management system. The choice of MicroPython determined by its simplicity and the availability of many ready-made web frameworks and libraries that facilitate the system development. For future applications, the system could be further modified and developed for precision agriculture.